Key Performance Indicators and Dimension of Organisational Strategic Approach - Abd Rahman Ahmad; Lim Chen Bin; Alaa S. Jameel; Hairul Rizad Md Sapry (Communications of International Proceedings, 2020)
This study provides the indispensable facts about the importance of the performance measurement for the organisation. Therefore, this paper will analyse one of the performance measurement tools – KPIs, by providing the theoretical details. After that, the strategy formed by the company to manage the KPIs will be identified. It helps to raise a milieu of awareness about the importance of implementation and maintenance of KPI among SMEs, particularly to the SMEs who are not aware about this. In addition, this study will serve as the basis for future plans of action by the SMEs. In this research, quantitative research methods were employed. This research is using a descriptive research design that seeks to describe the current status of SMEs implement the KPIs. A structured-questionnaire survey were used to collect the quantitative data by email and interview. The questionnaire of this research includes 5 sections. Multiple choices questions and Likert Scale questions were included in the questionnaire to collect the data. The questionnaire survey was developed in an easy-to-answer manner by providing options to survey participant. There are 155 SMEs that are registered with SME Corp. Malaysia in Batu Pahat, Johor. After all the completed questionnaires are collected from the respondent, 10 respondents’ data is carried out to ensure the accuracy and the suitability of this research. After that, all the data were analysed by using the Statistical Package for the Social Science (SPSS) version 21.0 to interpret the data using descriptive and inferential statistics. This study helps to identify the significant relationship between the SME’s strategic approach towards managing the business performance in their organisational strategy.